An Information-Theoretic Approach for Evaluating Probabilistic Tuning Functions of Single Neurons - Brostek, Lukas; Eggert, Thomas; Ono, Seiji; Mustari, Michael J.; Büttner, Ulrich; Glasauer, Stefan (Frontiers in Computational Neuroscience, 2011)
Neuronal tuning functions can be expressed by the conditional probability of observing a spike given any combination of independent variables. However, accurately determining such probabilistic tuning functions from experimental data poses several challenges such as finding the right combination of independent variables and determining their proper neuronal latencies. Here we present a novel approach of estimating and evaluating such probabilistic tuning functions, which offers a solution for these problems. By maximizing the mutual information between the probability distributions of spike occurrence and the variables, their neuronal latency can be estimated and the dependence of neuronal activity on different combinations of variables can be measured. The method was used to analyze neuronal activity in cortical area MSTd in dependence on signals related to eye and retinal image movement. Comparison with conventional feature detection and regression analysis techniques shows that our method offers distinct advantages, if the dependence does not match the regression model.